ON ℐ^𝒦-CONVERGENCE OF SEQUENCES OF BI-COMPLEX NUMBERS - J. Hossain; S. Debnath (Проблемы анализа)
We propose the concept of ℐ^𝒦-convergence of sequences of bi-complex numbers. We explore the fundamental properties of this newly introduced notion and its relationships with other convergence methods